Life cycle validation study of algal biofuels in Philippines via CML impact assessment - Ubando, Aristotle T. (Animo Repository, 2016)
Biodiesel is seen as one of the promising alternatives for fossil-based fuels while reducing the carbon dioxide emissions. However, as first generation biodiesels are derived from food crops, the concern on food versus fuel heightens. As such, algal biodiesel is perceived as a solution to this problem, due to its lesser land requirement while having high oil yield compared to biofuels derived from conventional feedstocks. As the Philippines is considered as a thriving habitat for numerous microalgae species in the tropics, it offers a big potential for algae biofuel production. However, like any other bioenergy system, algal biofuels require natural resource consumption and entails environmental impact. Hence, a life cycle assessment approach is proposed in this study to assess the current microalgae cultivation setup in the Philippines. A validation study is conducted to compare the results of an aquaculture setup in the Philippines and a cultivation system by Khoo et al. (2011). The functional unit used is 1 ton algal biodiesel. The results of the study revealed that the cultivation system found in the Philippines has performed well as compared to Khoo et al. (2011), in terms of the impact assessment and energy consumption. However, the study also found that the energy return on energy invested (EROEI) of the two models were less than the benchmark value of one. Thus, the result of this study can be used to improve the EROEI of the algal biodiesel life cycle in the Philippines. © 2015 IEEE.